ANALISIS STRATEGI OPERASIONAL, INOVASI PRODUK, DAN PROMOSI PADA PERLUASAN USAHA ES TELLER GLOBAL METRO - Gita Cahyani, Abel (YHMM PUBLISHING, 2025)
The traditional fresh beverage industry, such as es teller, has experienced rapid growth in response to rising consumer interest in innovative and high-quality local products. In an increasingly competitive market, business actors must not only maintain product quality but also develop efficient operational strategies, create appealing product innovations, and implement effective promotions. This study examines the strategic efforts of the Micro, Small, and Medium Enterprise (MSME) Es Teller Global Metro in expanding its market reach and increasing its competitiveness. Using a descriptive qualitative approach through observation, interviews, and documentation, the research found that business growth was driven by three main factors: operational efficiency, continuous product innovation aligned with market preferences, and consistent digital promotion across social media platforms. This integrated approach allowed the business to reach a broader customer base and retain customer loyalty. The findings offer practical insights for other MSMEs seeking to develop adaptive and sustainable business strategies in the dynamic culinary market.